2020
DOI: 10.3389/fspor.2020.00084
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Exercise Addiction in the Presence vs. Absence of Indicated Eating Disorders

Abstract: Despite the many benefits of regular, sustained exercise, there is evidence that exercise can become addictive, to the point where the exerciser experiences negative physiological and psychological symptoms, including withdrawal symptoms upon cessation, training through injury, and the detriment of social relationships. Furthermore, recent evidence suggests that the etiology of exercise addiction is different depending on the presence or absence of eating disorders. The aim of this study was to explore to what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Therefore, further research is needed in which larger samples with EA will be compared with an equal number of healthy, non-addicted controls. Our prevalence rate of 4.2% is comparable with the numbers that have been reported by Lichtenstein and Jensen (2016) for CrossFit athletes and by Ziemainz et al (2013) for endurance athletes, but it is much lower than the number of about 30.7% that has been reported by Trott et al (2020). However, the number of participants who were at risk for EA development was >80% in our study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, further research is needed in which larger samples with EA will be compared with an equal number of healthy, non-addicted controls. Our prevalence rate of 4.2% is comparable with the numbers that have been reported by Lichtenstein and Jensen (2016) for CrossFit athletes and by Ziemainz et al (2013) for endurance athletes, but it is much lower than the number of about 30.7% that has been reported by Trott et al (2020). However, the number of participants who were at risk for EA development was >80% in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Exercise addiction belongs to the non-substance-related addictions and has not yet been part of common classification systems. Divergent prevalence rates for EA have been reported for different groups [e.g., 1-3% (Stoll, 2017), 4.5% (Ziemainz et al, 2013), 5% (Lichtenstein and Jensen, 2016), or 30.7% (Trott et al, 2020)]. Exercise addiction is-just like other addictions-accompanied by withdrawal symptoms if too long breaks are taken, tolerance development, and loss of control (Breuer and Kleinert, 2009;Ziemainz et al, 2013;Stoll, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The connection between the risk of exercises addiction and overexercising for the sake of diet and weight control is difficult to untangle. The risk of exercise addiction occurs three and a half times more frequently, as a co-morbidity in people suffering of some sort of eating disorder in contrast to individuals without an eating disorder (Trott et al, 2020 ). Exaggerated exercise in the latter group is known as primary exercise addiction, in which exercise fulfillment is the reward itself, while in various eating disorders exercise is only an additional means (above diet, purging, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In particular, because it has been suggested that healthy exercise and MEB (at least as operationalised in the currently available assessment instruments) may share some of their attributes [ 68 , 69 ]. Indeed, this circumstance has led some authors to suggest the need to control by exercise volume or even by perceived health status when examining the relationship between MEB and its potential antecedents [ 69 , 70 , 71 ]. However, it should be noted that these two factors were not taken into account when computing the original effect sizes retrieved in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A clear example would be the clinical nature of the sample in terms of eating disorders. In particular, since associations between MEB and variables involving a negative evaluation of the body have been found to be weaker among individuals at high-risk relative to those at low-risk of developing eating disorders [ 70 ]. Therefore, further research aimed at examining the relationship between body dissatisfaction and MEB among individuals at high-risk of eating disorders appears warranted.…”
Section: Discussionmentioning
confidence: 99%